Apa Penyebab Ketimpangan Pendapatan Di Pulau Jawa? - Anney Crismestika; Raden Parianom (Fakultas Ekonomi Dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Indonesia's economic activities are mostly centered on the island of Java, as indicated by the value of economic growth which is always recorded at the top compared to other islands. The flourishing of economic activity that occurs does not go hand in hand with the welfare of the people, in fact income inequality on the island of Java is the highest, this is of course caused by several factors. The aim of this research is to determine the factors that are thought to influence income inequality in each province on the island of Java for the period 2016-2021, including the variables Financial Inclusion, Gross Regional Domestic Product (GRDP) Per Capita, and Human Development Index (HDI). The total sample used was 36 data obtained from the Central Statistics Agency and Bank Indonesia. The analysis used is panel data regression analysis with the best model, namely the Fixed Effect Model (FEM), which was then developed into Feasible Generalized Least Square (FGLS). Partial research results show that GRDP per capita negatively and significantly influences income inequality, HDI positively and significantly influences income inequality, while financial inclusion does not positively and significantly influence income inequality. Meanwhile, all independent variables simultaneously influence income inequality on the island of Java. Keywords: Income Inequality, Financial Inclusion, GRDP Per Capita, Human Development Index Abstrak Tujuan dilakukan penelitian ini adalah untuk mengetahui faktor-faktor yang diduga berpengaruh terhadap ketimpangan pendapatan pada setiap provinsi di Pulau Jawa periode 2016 – 2021, antara lain variabel Inklusi Keuangan, Produk Domestik Regional Bruto (PDRB) Perkapita, dan Indeks Pembangunan Manusia (IPM). Total sampel yang digunakan adalah 36 data yang diperoleh dari Badan Pusat Statistik dan Bank Indonesia. Analisis yang digunakan yakni analisis regresi data panel dengan model terbaik yaitu Fixed Effect Model (FEM) yang kemudian dikembangkan menjadi Feasible Generalized Least Square (FGLS). Hasil penelitian secara parsial didapatkan bahwa PDRB Perkapita secara negatif signifikan mempengaruhi ketimpangan pendapatan, IPM secara positif signifikan mempengaruhi ketimpangan pendapatan, sedangkan inklusi keuangan secara positif tidak signifikan mempengaruhi ketimpangan pendapatan. Adapun secara simultan seluruh variabel bebas berpengaruh terhadap ketimpangan pendapatan di Pulau Jawa. Kata Kunci: Ketimpangan Pendapatan, Inklusi Keuangan, PDRB Perkapita, Indeks Pembangunan Manusia